Narasi Keadilan dan Emosi Sosial dalam Pemberitaan Kematian Affan Perspektif Retorika Aristoteles - Dede Putri; Desma Yuliadi Saputra; Rina Andriani (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The news of the death of Affan Kurniawan, an online motorcycle taxi driver who lost his life in clashes during demonstrations in Jakarta, sparked an extraordinary public reaction and gave rise to the narrative of